Damping of Linear Nonadiabatic MHD Waves in a Flowing Prominence Medium - Nagendra Kumar; Anil Kumar; Himanshu Sikka; Pradeep Kumar (Advances in Astronomy)
We study the effect of shear flow on the time damping of linear nonadiabatic magnetoacoustic waves in a solar prominence. We consider a homogeneous, isothermal, and unbounded medium permeated by a uniform magnetic field. The adiabaticity is removed by including the optically thin radiative losses, thermal conduction, and heating term in energy equation. We present a local theory of MHD waves to obtain a dispersion relation. The dispersion relation is solved numerically to study the time damping of these waves. It is found that flow influences the damping time and damping per period of both the slow and fast waves significantly. Damping time and damping per period of slow waves are very much higher than the damping time and damping per period of fast waves.